До завтра надо : * разложите на множители: y²-4y+4= 36x⁴y²-169c⁴= (x+1)²-(2x-1)²= выражение: (c+6)²-c(c+12)=

КристинаСтерликова КристинаСтерликова    3   27.08.2019 04:30    2

Ответы
As337 As337  05.10.2020 22:09
У^2 - 4у + 4 = ( у - 2 )^2
36х^4у^2 - 169с^4 = ( 6х^2у )^2 - ( 13с^2 )^2 = ( 6х^2у - 13с^2 )•( 6х^2у + 13с^2 )
( Х + 1 )^2 - ( 2х - 1 )^2 = ( Х + 1 + 2х - 1 )•( Х + 1 - 2х + 1 ) = 3х•( 2 - Х )
( с + 6 )^2 - с( с + 12 ) = с^2 + 12с + 36 - с^2 - 12с = 36
ПОКАЗАТЬ ОТВЕТЫ
ник5030 ник5030  05.10.2020 22:09
Разложил:
y²-4y+4=  (y-2)^{2}
36x⁴y²-169c⁴= -( 13c^{2} - 6 x^{2} y) ( 13c^{2} + 6 x^{2} y)
(x+1)²-(2x-1)²= -3(x-2)x

Упростил:
(c+6)²-c(c+12)= 36
ПОКАЗАТЬ ОТВЕТЫ